2019
DOI: 10.1111/nph.15620
|View full text |Cite
|
Sign up to set email alerts
|

Cotton fiber elongation requires the transcription factor GhMYB212 to regulate sucrose transportation into expanding fibers

Abstract: Summary Cotton is white gold across the globe and composed of fiber cells derived from the outer integument of cotton ovules. Fiber elongation uses sucrose as a direct carbon source. The molecular mechanism transcriptionally controlling sucrose transport from ovules into the elongating fibers remains elusive. In this study the involvement of GhMYB212 in the regulation of sucrose transportion into expanding fibers was investigated. GhMYB212 RNAi plants (GhMYB212i) accumulated less sucrose and glucose in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 63 publications
5
67
0
Order By: Relevance
“…Furthermore, analysis of the cis-elements in the promoter of 22 speci cally expressed genes revealed that NAC, MYB and WRKY transcription factors binding sites were localized in all the promoters. This result indicted that MYB, NAC and WRKY transcription factors might regulate the expression of GhCrRLK1Ls during ber development, which was consistent with the previous reports that MYB transcription factors such as GhMYB109, GhMYB25, GhMYB25-like and GhMYB212 play vital roles in ber development [15,16,18,32]. The functions of NAC and WRKY transcription factors in ber development need further research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, analysis of the cis-elements in the promoter of 22 speci cally expressed genes revealed that NAC, MYB and WRKY transcription factors binding sites were localized in all the promoters. This result indicted that MYB, NAC and WRKY transcription factors might regulate the expression of GhCrRLK1Ls during ber development, which was consistent with the previous reports that MYB transcription factors such as GhMYB109, GhMYB25, GhMYB25-like and GhMYB212 play vital roles in ber development [15,16,18,32]. The functions of NAC and WRKY transcription factors in ber development need further research.…”
Section: Discussionsupporting
confidence: 90%
“…SiRNA derived from NATs participated in posttranscription gene silencing of GhMML3_A12, which leads to the fuzzless phenotype in N1 mutant [16,17]. Besides these, silencing of GhMYB212 or GhSWEET12 in cotton results in the accumulation of sucrose and glucose in ber, short ber length and decreased lint percentage [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose also functions as a signal in the regulation of strawberry fruit development and ripening (Jia et al, 2013). Sugar transport during seed development is also required for fibre elongation in cotton (Sun et al, 2018). On the basis of annotations in the 'Tunisia' genome, the PgL0145770 and PgL0145810 genes on chromosome 3 in the soft-seeded population were determined to encode the sucrose transport proteins SUC8-like and SUC6, respectively (Figure 4a).…”
Section: Selective Genes Mediating Sucrose Transportmentioning
confidence: 99%
“…The secondary expansion of epidemic cells is initiated after 7 to 10 DPA, and these cells gradually develop into fuzz that is attached to the surface of a seed [55][56][57]. Factors that influence the initiation, differentiation, and development of fibers include phytohormones, such as IAA and GA, and brassinolactone, as well as transcription factors [58][59][60][61]. The arrangement of cellulose deposition plays an important role in the formation of fiber strength and fineness [62,63].…”
Section: Functional Biodiversity Of Fbp Genes In Gossypium Speciesmentioning
confidence: 99%